2018
DOI: 10.1037/ser0000207
|View full text |Cite
|
Sign up to set email alerts
|

Relation between sexual and gender minority status and suicide attempts among veterans seeking treatment for military sexual trauma.

Abstract: There is limited study of suicidal behaviors among veterans identifying as sexual and gender minorities (SGMs), despite previous research indicating rates of suicide attempts are high within civilian SGM populations. Further, some research incorporating military service members suggests those identifying as SGMs are disproportionately exposed to military sexual trauma (MST), an additional risk factor for negative psychiatric sequelae. To address health care research disparities among minority veterans (i.e., w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…For example, Sexton et al reported higher rates of suicide attempts among SM Veterans who experienced MST compared with non-SM Veterans with MST. 41 In our study, SM women were twice as likely to report MST than non-SM women Veterans (43% vs. 21%), which aligns with prior VHA survey research from 2013 (31% vs. 13%). 42 The low occurrence of SM documentation in primary care settings is concerning but coincides with recent research outside the VHA.…”
Section: Sexual Orientation Documentationsupporting
confidence: 87%
“…For example, Sexton et al reported higher rates of suicide attempts among SM Veterans who experienced MST compared with non-SM Veterans with MST. 41 In our study, SM women were twice as likely to report MST than non-SM women Veterans (43% vs. 21%), which aligns with prior VHA survey research from 2013 (31% vs. 13%). 42 The low occurrence of SM documentation in primary care settings is concerning but coincides with recent research outside the VHA.…”
Section: Sexual Orientation Documentationsupporting
confidence: 87%
“…Furthermore, only two studies examined these relations among transgender veterans (Beckman et al, 2018; Brown & Jones, 2015). More research is needed to examine MST across diverse military groups, especially considering that MST-exposed veterans from marginalized groups may be at greater risk of certain risky behaviors (i.e., suicide; Sexton et al, 2018). Thus, more research is needed to examine the associations of MST and risky behaviors among diverse military groups to better inform prevention and treatment efforts.…”
Section: Discussionmentioning
confidence: 99%
“… 6 In addition, recent findings suggest that MST survivors who identify as a sexual and/or gender minority are more likely to report a history of suicide attempt than non-gender/sexual minority MST survivors. 55 As such, it will be important for future research to extrapolate the role of gender and to consider a non-gender binary lens, as well as sexual orientation, in these associations. Moreover, understanding more about veterans’ experiences disclosing their worst traumatic events and the actual responses to such disclosures is essential.…”
Section: Discussionmentioning
confidence: 99%